The Influence Mechanism of Pore Structure of Tectonically Deformed Coal on the Adsorption and Desorption Hysteresis - Ren, Jiangang; Weng, Hongbo; Li, Bing; Chen, Feng; Liu, Jianbao; Song, Zhimin (Frontiers in Earth Science, 2022)
Pore is the main adsorption and desorption space of coalbed methane (CBM). Pore size configuration and connectivity affect the adsorption/desorption hysteresis effect. Using tectonically deformed coal (TDC) and original structure coal of medium- and high-rank coal as the research objects, through the N2/CO2 adsorption experiment to analyse the pore size distribution and connectivity of different scales. We investigate the control mechanism of heterogeneous evolution in the key pore scales against adsorption/desorption hysteresis characteristics during coal metamorphism and deformation by combining the CH4 isothermal adsorption/desorption experiment under 30°C equilibrium moisture. The findings indicate that the super micropores (<2 nm) are mainly combination ink bottle-shaped pores, have worse connectivity as the degree of metamorphism and deformation increases. The super micropores occupy the vast majority of pore volume and specific surface area, its pore size distribution curve change presents an “M” bimodal type, is mainly concentrated in two-pore segments of 0.45–0.70 nm and 0.70–0.90 nm. The effect of ductile deformation exerts a significantly greater effect on super micropores than brittle deformation. The exhibited adsorption–desorption characteristics are the result of the combined effect of the unique pore structure of the TDCs and different moisture contents. The presence of a large number of super micropores is the most important factor influencing the degree of gas desorption hysteresis. The “ink-bottle effect” is the primary cause of gas desorption hysteresis. For CBM development, some novel methods to increase desorption and diffusion rate at the super micropores scale should be considered.